'A constant menace to British interests': changing attitudes towards 'German schools' during World War I. Issue 2 (3rd April 2019) - Carden, Clarissa
Abstract: This article draws on archival materials and newspaper reports in order to provide an account of the closure of 'German schools' in Queensland during the First World War. Prior to 1915, German Lutheran students enrolled at state schools were permitted to take time off to attend German schools, often run by German ministers of religion, in order to preserve cultural and linguistic traditions. From 1915, however, this practice was forbidden. This article shines a light on the local factors that differentiated the story of German schools in Queensland from that of other Lutheran schools in Australia.